IMPACT OF PREOPERATORY MAGNETIC RESONANCE IMAGING IN ONCOPLASTIC SURGERY - Anselmi, Karina Furlan; Urban, Cicero; Urban, Linei; Sebastião, Ana Paula Martins; Lima, Rubens; Kuroda, Flavia; Spautz, Cleverton; Martins, Thiago Astorga; Rabinovich, Iris; Schunemann, Eduardo (Mastology, 2017)
Objective: There is no data about magnetic resonance image (MRI) impact in oncoplastic surgery (OP). The objective of this study was to evaluate the impact of MRI on the surgical planning and the changes of conduct in patients with initial breast cancer and candidates to perform the OP. Methods: This is a prospective cohort of 60 patients who were candidates to OP between January 2013 and July 2014. All of them underwent to a preoperative MRI, in addition to mammography (MG) and ultrasound (US). Any additional tumor in the MRI classified as BIRADS 4-5 were biopsied or marked with carbon and radiotracer in order to be localized during the surgery. Surgical impact of additional MRI findings were evaluated as to changes of approach to mastectomy or to wider resection. Results: Of the patients, 29/60 (48.3%) had additional findings on MRI, 16/29 (55%) were multifocal tumors, 1/29 (3.4%) was multicentric, 5/29 (17%) were contralateral tumors, and 9/29 (31%) presented tumor size larger than 10 mm in the MRI. Of 22 patients who showed additional lesions on MRI, 15 (68.2%) had invasive carcinomas in the definitive anatomopathological exam. Sensibility of MRI was higher in the estimation of the tumor size. Of the patients, 12/60 (20%) underwent to mastectomy, and 17/60 (28.3%) to wider resections. Only 5% of patients had positive margins in the entire group, and in the group of patients that had additional findings on MRI only 3.4% had positive margins. Conclusions: MRI is better than MG and US in evaluating the extension of the tumor, and in the detection of multicentricity, multifocality and bilaterality. In consequence, it contributed in this series for a better surgical planning in OP with a low rate of compromised margins and re-operations.